Comparison of short-term outcomes between robotic and laparoscopic distal gastrectomy performed by the same surgical team during the same period - Shen, Jiliang; Feng, Xu; Li, Zheyong; Wang, Yong (Frontiers in Oncology, 2023)
Objective To evaluate the short-term outcomes of laparoscopic distal gastrectomy and robotic distal gastrectomy performed during the same period. Methods This study enrolled 46 cases of laparoscopic distal gastrectomy and 67 cases of robotic distal gastrectomy that were performed by a single surgeon between April 2020 to October 2021. Baseline characteristics and short-term outcomes of these two groups were then compared. Moreover, the robotic distal gastrectomy group was further divided into two subgroups according to the learning curve. Finally, the baseline characteristics and short-term outcomes of both subgroups were compared with the laparoscopic group, respectively. Results The baseline characteristics and short-term outcomes of the LDG group and RDG group were comparable. In contrast, the operation time in the laparoscopic group was significantly shorter than that in the early experience robotic group (191.3 ± 37.6 VS 225.1 ± 49, P=0.001). However, the operation time (191.3 ± 37.6 VS 185.3 ± 25.3, P=0.434) was comparable between the laparoscopic group and the late experience robotic group. Likewise, the bleeding volume was comparable between the laparoscopic and early experience robotic groups. However, bleeding volume was significantly lower in the late experience robotic group compared to that in the laparoscopic group (37.5 ± 18.8 VS 49.2 ± 29.0, P=0.049). Conclusions With surgeons stepping into the stable stage of the robotic learning curve, RDG showed a comparable operation time and lower volume of blood loss compared with LDG. Collectively, our study supports the application of robotic distal gastrectomy in patients diagnosed with gastric cancer.